Cytosolic DNA sensors activation of human astrocytes inhibits herpes simplex virus through IRF1 induction - Liu, Yu; Xu, Xi-Qiu; Li, Wei-Jing; Zhang, Biao; Meng, Feng-Zhen; Wang, Xu; Majid, Safah M.; Guo, Zihan; Ho, Wen-Zhe (Frontiers in Cellular and Infection Microbiology, 2024)
While astrocytes participate in the CNS innate immunity against herpes simplex virus type 1 (HSV-1) infection, they are the major target for the virus. Therefore, it is of importance to understand the interplay between the astrocyte-mediated immunity and HSV-1 infection. In this study, we examined whether activating DNA sensors of astrocytes can elicit the intracellular immune response to HSV-1 infection. We demonstrated that poly(dA:dT) (a synthetic ligand for the DNA sensors) could inhibit HSV-1 replication and induce IFN-β/IFN-λ production in human astrocytes. Poly(dA:dT) treatment of astrocytes also induced the expression of IFN-stimulated antiviral genes (Viperin, ISG56 and MxA).Among IFN regulatory factor (IRF) members examined, poly(dA:dT) selectively upregulated IRF1 and IRF9, particularly IRF1 in human astrocytes. The inductive effects of poly(dA:dT) on IFNs and ISGs were diminished in the IRF1 knockout cells. In addition, IRF1 knockout attenuated poly(dA:dT)-mediated HSV-1 inhibition in the cells. These observations indicate that the cytosolic DNA sensors have a protective role in astrocyte intracellular innate immunity against HSV-1 and that targeting the DNA sensors has potential for immune activation-based HSV-1 therapy.